Effectiveness of Urban Parks in Reducing Surface Temperatures in Riyadh City Using Remote Sensing and Geographic Information Systems - Al-Shahrani, Haya Falah (Journal of natural sciences, life and applied sciences, 2025)
This study aims to analyze the environmental role of urban parks in Riyadh in mitigating the Urban Heat Island (UHI) phenomenon by evaluating the impact of vegetation cover and green spaces on lowering surface temperatures. The study relies on the analysis of satellite imagery captured by Landsat for the years 2014 and 2020, alongside the use of Google Earth to locate parks, which were subsequently processed using Geographic Information Systems (GIS) and statistical analysis methods. The relationship between vegetation distribution within the parks and its influence on temperatures in the surrounding areas within a 500-meter radius was examined. The results revealed clear differences in the environmental impact of parks. Parks such as Al-Salam Park and King Abdulaziz Historical Center Park showed a significant temperature reduction of up to 6.72°C, attributed to dense vegetation and the presence of water bodies. In contrast, some parks with limited vegetation, such as Abu Dhar Al-Ghafari Park and Al-Rawda Park, were not effective in cooling, and even showed negative thermal effects due to high proportions of impervious surfaces and sparse tree coverage. The study concludes that the effectiveness of parks in reducing surface temperatures is primarily dependent on their design and the distribution of vegetation and water elements within them. The findings underscore the importance of integrating environmental considerations into urban planning and promoting policies that support the development and maintenance of green spaces as a vital tool for enhancing local climate and quality of life in arid cities.
Keywords: Urban Cooling; Vegetation Cover; Urban Climate; Saudi Arabia